On Meanings and Descriptions - Mieke Bal (Studies in 20th & 21st Century Literature, 1981)
Although descriptive passages would appear to be of marginal importance in narrative texts, they are, in fact, of both logical and semantic necessity. Narratology, therefore, must take these segments into account. In this article, I shall survey the present situation in this field and compare rival points of view. I shall also offer several suggestions for analyzing descriptions. The following topics will be discussed: the nature of description as a specific type of discourse which makes it recognizable as such; the internal structure of description; the place and function of descriptions in the text as a whole. In the latter section, the semantic impact of descriptions in the overall meaning of narrative texts will be accounted for. This article is intended as a contribution to the theory of description as a part of narratology. It also has a didactic purpose, since it proposes a model for the analysis of texts which can be used for systematic text-study, both in a historical and a comparative perspective.
Keywords: descriptive passages; narratology; description analysis; nature of description; discourse; internal structure of description; description; semantics; meaning; theory of description; textual analysis; comparative; historical